2022
DOI: 10.3389/fpubh.2022.987276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture on the pregnancy outcomes of frozen-thawed embryo transfer: A systematic review and meta-analysis

Abstract: BackgroundAcupuncture is increasingly used as adjuvant therapy for infertile women undergoing frozen-thawed embryo transfer (FET); however, its effects and safety are highly controversial. This study aimed to evaluate the pooled effects of adjuvant acupuncture on FET pregnancy outcomes.MethodsWe considered only randomized controlled trials (RCTs) that compared acupuncture with sham acupuncture or no adjuvant treatment during FET and the primary outcome was clinical pregnancy rate. Two authors separately select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…[37][38][39][40] Acupuncture is a mild treatment with relatively fewer adverse reactions and costs. 41 Although acupuncture is associated with adverse effects such as hypodermal haemorrhage, in contrast to the gastrointestinal adverse effects associated with NSAIDs, acupuncture may be an alternate approach for patients who cannot endure the harmful effects on the digestive system. 42 Acupuncture exerts its analgesic properties through the regulation of affective and cognitive processing regions of the brain, as well as by stimulating endorphins, serotonin, and acetylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40] Acupuncture is a mild treatment with relatively fewer adverse reactions and costs. 41 Although acupuncture is associated with adverse effects such as hypodermal haemorrhage, in contrast to the gastrointestinal adverse effects associated with NSAIDs, acupuncture may be an alternate approach for patients who cannot endure the harmful effects on the digestive system. 42 Acupuncture exerts its analgesic properties through the regulation of affective and cognitive processing regions of the brain, as well as by stimulating endorphins, serotonin, and acetylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…However, in two other systematic evaluations, acupuncture was found to improve clinical pregnancy during IVF [30,31]. Another study confirmed that acupuncture before or during FET helped improve patients' biochemical pregnancy, and clinical pregnancy outcomes and the risk of serious adverse events is very low [32]. However, no significant improvement of acupuncture for live birth during FET was reported.…”
Section: Acupuncture Management For the Pregnancy Outcomesmentioning
confidence: 96%
“…Several systematic reviews and meta-analyses have attempted to synthesize the available data. While some failed to show any benefit (25,26), most of the recent ones, have reported a positive an impact of acupuncture on fertility and IVF outcomes (27)(28)(29)(30).…”
Section: Acupuncturementioning
confidence: 98%